2006
DOI: 10.1111/j.1743-6109.2006.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Induced Inhibition of Genital Vascular Responses is Reversed by Vardenafil in Female Rabbits

Abstract: Introduction Administration of serotonin reuptake inhibitors (SRI) or serotonin and norepinephrine reuptake inhibitors (SNRI) relieves depressive symptoms but may cause sexual dysfunction in women and men. Aim The aim of the present study was to evaluate the effects of the phosphodiesterase type 5 (PDE5) inhibitor, vardenafil, on inhibition of genital vascular responses (GVR) induced by SRI or SNRI administration in female ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Although the treatment of FSAD has various options including hormone therapy, phosphodiesterase (PDE) inhibitors and alphablockers, mostly through enhancement of the vaginal blood flow [6,[8][9][10][11][12][13], they possess undesired side effects following their systemic administration. For examples, since PDE inhibitors and ablockers affected the systemic blood pressure and cardiac function, their clinical usages often resulted in adverse activities in cardiovascular regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the treatment of FSAD has various options including hormone therapy, phosphodiesterase (PDE) inhibitors and alphablockers, mostly through enhancement of the vaginal blood flow [6,[8][9][10][11][12][13], they possess undesired side effects following their systemic administration. For examples, since PDE inhibitors and ablockers affected the systemic blood pressure and cardiac function, their clinical usages often resulted in adverse activities in cardiovascular regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Angulo et al [30] examined the effects of PDE5 inhibition of genital vascular responses induced by serotonin reuptake inhibitors or serotonin and norepinephrine reuptake inhibitors. Vaginal and clitoral vasodilatory responses were measured to pelvic nerve electrical stimulation by laser Doppler fl ow needle probes.…”
Section: Basic Science Investigation Of Female Sexual Dysfunctionmentioning
confidence: 99%
“…Treatment with PDE5 inhibitor completely reversed the inhibition of genital vascular responses induced by paroxetine, venlafaxine, or duloxetine. They concluded that PDE5 inhibition may represent a reasonable approach to treat antidepressant-induced female sexual dysfunction, in particular, arousal disorders [30].…”
Section: Basic Science Investigation Of Female Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracavernous pressure and blood flow can be measured by inserting a probe into vaginal tissue and the corpus cavernosum, and signals to a laser Doppler blood flow monitor and thus, following PNS, changes in vaginal and clitoral blood flow can be measured. Recently, Angulo and colleagues demonstrated that treatment with vardenafil, a PDE5 inhibitor, increased vaginal and clitoral blood flow following PNS, which was assessed by laser Doppler, in a FSD-rabbit model where the animals were treated with anti-depressants [25]. The use of the female New Zealand white rabbit has given tremendous insight into genital hemodynamic measurements.…”
Section: Introductionmentioning
confidence: 99%